2006
DOI: 10.1016/j.ymthe.2006.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The integration profile of EIAV-based vectors

Abstract: Lentiviral vectors based on equine infectious anemia virus (EIAV) stably integrate into dividing and nondividing cells such as neurons, conferring long-term expression of their transgene. The integration profile of an EIAV vector was analyzed in dividing HEK293T cells, alongside an HIV-1 vector as a control, and compared to a random dataset generated in silico. A multivariate regression model was generated and the influence of the following parameters on integration site selection determined: (a) within/not wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 31 publications
6
54
0
Order By: Relevance
“…Estimation of integrated HIV copies by quantitative PCR (Fig. 5B) (16,63). EIAV integration sites were analyzed as described previously (17), yielding a total of 4923 integration sites.…”
Section: Generation Of Ledgf/p75mentioning
confidence: 99%
“…Estimation of integrated HIV copies by quantitative PCR (Fig. 5B) (16,63). EIAV integration sites were analyzed as described previously (17), yielding a total of 4923 integration sites.…”
Section: Generation Of Ledgf/p75mentioning
confidence: 99%
“…It has been shown that EIAV vectors preferentially integrate within active genes favoring AT-rich regions with a similar profile to that of HIV-1 vectors. 54 Furthermore, it has recently been demonstrated that the genotoxicity associated with lentiviral vectors is very low. 55 In conclusion, treatment of mouse models with lentiviral vectors carrying a reporter gene and/or the therapeutic gene, ABCA4, results in high-level and sustained expression of a transgene/protein in the injected area.…”
Section: Discussionmentioning
confidence: 99%
“…75 HIV-1 or EIAV vectors in vitro, for example, consistently favour integration into active coding regions in dividing human cell lines, unlike retroviral MoLV vectors, which favour integration near transcriptional start sites. [76][77][78] HIV-1 integration in (post-mitotic) murine or rat RPE in vivo does not appear to show site preference for these regions, and instead shows near-random and uniform frequency of integration into genes and gene spare long interspersed nuclear elements, 79 suggesting that the risk of integrating HIV-1-related IM in post-mitotic tissues is probably low, and lower than in mitotically active cells. The in vivo intraocular vector integration profiles of lentiviruses other than HIV-1 have not been reported, but are also likely to be influenced by the degree of target cell mitosis.…”
Section: Posterior Segment Applicationsmentioning
confidence: 99%